Translated Long Non-Coding Ribonucleic Acid ZFAS1 Promotes Cancer Cell Migration by Elevating Reactive Oxygen Species Production in Hepatocellular Carcinoma - Guo, Zhi-Wei; Meng, Yu; Zhai, Xiang-Ming; Xie, Chen; Zhao, Na; Li, Min; Zhou, Chun-Lian; Li, Kun; Liu, Tian-Cai; Yang, Xue-Xi; Wu, Ying-Song (Frontiers in Genetics, 2019)
Micropeptides (≤ 100 amino acids) are essential regulators of physiological and pathological processes, which can be encoded by small open reading frames (smORFs) derived from long non-coding RNAs (lncRNAs). Recently, lncRNA-encoded micropeptides have been shown to have essential roles in tumorigenesis. Since translated smORF identification remains technically challenging, little is known of their pathological functions in cancer. Therefore, we created classifiers to identify translated smORFs derived from lncRNAs based on ribosome-protected fragment sequencing and machine learning methods. In total, 537 putative translated smORFs were identified and the coding potentials of five smORFs were experimentally validated via construct generation and mass spectrometry. After analyzing 11 lncRNA expression profiles of seven cancer types, we identified one validated translated lncRNA, ZFAS1, that was significantly differentially expressed in hepatocellular carcinoma (HCC). Functional studies revealed that ZFAS1 can promote cancer cell migration by elevating intracellular reactive oxygen species production by inhibiting NADH dehydrogenase expression, indicating that translated ZFAS1 is an essential oncogenic event in the progression of HCC. In this study, we systematically identified translated smORFs from lncRNAs and explored their potential pathological functions in cancer to improve our comprehensive understanding of the building blocks of living systems.